Life review on psychospiritual outcomes among older adults with life-threatening illnesses: A systematic review and meta-analysis - Liu, Mandong; Wang, Ying; Du, Yan; Chi, Iris (Frontiers in Psychiatry, 2023)
Background: At the intersection of old age and illness, older adults with life-threatening illnesses (LTI) are a group who often show resilience and seek validation of life, acceptance, and integration of past and now, even under the fear of loss, suffering, and dying evoked by life adversities. Life review has been widely conducted to help older adults enhance well-being and cope with burdens. Spirituality is an important part of an older adult’ overall well-being, especially for those with LTI. However, few review studies examined the effectiveness of life review interventions on psychospiritual outcomes among this population. The aim of the study was to examine the effectiveness of life review on psychospiritual well-being among older adults with LTI. Methods: A systematic review with meta-analysis following the recommendations of the Cochrane Collaboration was conducted. Database searches included PubMed, PsycINFO, the Cochrane Library, the Campbell Library, EBSCO, CNKI, and the Airiti Library up to March 2020. Grey literature and reference lists from relevant articles were also searched and reviewed. Results: 34 studies were included in the systematic review and the meta-analysis for outcomes of depression (n=24), quality-of-life (QOL) (n=10), anxiety (n=5), life satisfaction (n=3), mood (n=3), apathy (n=2), and general well-being (n=2). Other psychospiritual outcome measures included spirituality, self-esteem, meaning in life, hope, and some multi-dimensional instruments. The studies greatly varied in program design, content, format, length, and more. Although with high heterogeneity, meta-analysis results demonstrated standardized mean differences in favor of life review in decreasing depression, anxiety, negative mood, and increasing positive mood and QOL compared with the control group. Conclusions: This review calls for including more psycho-spiritual well-being measures among interventions for older adults with LTI, as well as studies with rigorous designs in future research.